Bahasa Indonesia: Between Freedom of Religion and Apostasy in Islam: Analysis of Surah Al-Baqarah Verse 256 - Armayanto, Harda; Dzulhadi, Qosim Nurseha; Ulfa, Maria (Center of Islamic and Occidental Studies, 2023)
This article aims to explain the concept of religious freedom in Islam. This concept is revealed in the Qur'an surah al-Baqarah verse 256, which states that religion has no compulsion. This verse is an affirmation that Islam upholds the values of tolerance and humanity, as well as an answer to the accusation that Islam is spread by the sword (violence). However, in practice, some people interpret this verse differently, that Islam allows its adherents to apostate. With the argument that apostasy is part of religious freedom. Based on that reason, this article analyzes sura al-Baqarah verse 256 based on the interpretations of classical and contemporary commentators, as well as analyzes the traditions of the Prophet Muhammad concerning apostasy and religious freedom. This article is qualitative in nature used library research for data collection from books, journals, and other documents related to the topic of discussion. The collected data were then analyzed using the critical-analysis method. The study found that religious freedom in Islam is related to the relationship between the servant and God. Muslims are not free to do something because they are bound by their obligations as servants. That is, Islam does not allow its adherents to apostatize because it violates God's teachings and also Islam does not force other people to embrace this religion.